Application of golden ratios in non-uniform linear array design - Huang, Yi (Nanyang Technological University, 2022)
Antenna arrays are the key technologies in applications such as radar, sonar and wireless communications. The design of antenna arrays to achieve desired performance involves trade-offs among the array geometry, the side lobe levels and main beamwidth.